Meta-Analysis of Sleep Deprivation Effects on Patients With Depression - Hu, Baiqi; Liu, Chunyan; Mou, Tingting; Luo, Fangyi; Lv, Tingting; Qian, Chao; Zhang, Jian; Ye, Mengfei; Liu, Zheng (Frontiers in Psychiatry, 2021)
Objective: Depression is a common disorder with a high recurrence rate. Since the effect of sleep deprivation on depression in existing studies were inconsistent, the present study aimed to reassess the effects of SD on patients by performing a meta-analysis of updated research. Methods: PubMed, Embase, the Cochrane Library, and Web of Science were searched for articles before January 20th, 2021. Data on participant characteristics, SD characteristics, adjunctive method and tests for depression were extracted. A comprehensive analysis was conducted to assess the effect of SD on depression and subgroup analysis was used to determine the sources of heterogeneity. Results: In total, 8 articles were included. An SD duration of less than 7 days slightly worsened depression levels [0.24 (-0.21, 0.69); I2 = 0%; P = 0.43], a duration of 7–14 days had antidepressant effects [-1.52 (-2.07, -0.97); I2 = 19.6%; P = 0.288], and a duration of more than 14 days also worsened depression [0.76 (0.12, 1.40); I2 = 43.7%; P = 0.169]. Conclusion: SD may serve as an effective antidepressant measure in humans when the duration is 7–14 days, while a duration of less than 7 days and more than 14 days worsened depression.